Work Disrupted - Schwartz, Jeff; Riss, Suzanne (Ascent Audio, 2021)
The future of work swept in sooner than expected, accelerated by Covid-19, creating an urgent need for new maps, new mindsets, new strategies-and most importantly, a trusted guide to take us on this journey. That guide is Jeff Schwartz. A founding partner of Deloitte Consulting's Future of Work practice, Schwartz brings clarity, humor, wisdom, and practical advice to the future of work, a topic surrounded by misinformation, fear, and confusion. If you're anxious about robots taking away your job in the future, you will take comfort in the realistic perspective, fact-based insights, and practical steps Schwartz offers. If you're not sure where to even begin to prepare, follow his level-headed advice and easy-to-follow action plans. If you're a business leader caught between keeping up, while also being thoughtful about the next moves, you will appreciate the playbook directed at you. Written in a conversational style by Schwartz, with Suzanne Riss, an award-winning journalist and book author, Work Disrupted offers a welcome alternative to books on the topic that lack a broad perspective or dwell on problems rather than offer solutions. Timely and insightful, the book includes the impact of Covid-19 on our present and future work. Interviews with leading thinkers on the future of work offer additional perspectives and guidance.